Análisis de la recaudación tributaria del Impuesto a la Renta, Impuesto al Valor Agregado, Impuesto a los Consumos Especiales e Impuesto a la Salida de Divisas del cantón Catamayo, periodo 2018-2022 - Vaca Cueva, Stefany Jhoana (2024)
The Curricular Integration Work called: Analysis of the tax collection of Income Tax, Value Added Tax, Special Consumption Tax and Tax on the Exit of Foreign Exchange in the canton Catamayo, period 2018-2022, has as objectives to identify and compare the different percentages and values collected of the four taxes of study in the canton Catamayo, during the period 2018-2022, for this the scientific, deductive, inductive, analytical and synthetic research methods were applied, and techniques such as observation, bibliographic compilation and statistics, which allowed the collection of information and data issued by the Internal Revenue Service on tax collection; With the quantitative information, tables and figures were prepared to facilitate the recognition of the existing increases and decreases in tax collection and, based on the legal and conceptual foundations, a comparison was made of the totals collected. Once the records of the Internal Revenue Service database were statistically represented, it became evident that the year with the highest tax collection was 2019, however, the taxes that stood out were Income Tax and Value Added Tax with values of $1. 342,038.17 and $1,395,667.99 respectively, on the other hand, the Special Excise Tax obtained its maximum collection in 2018 with $53,687.01 and the Tax on the Exit of Foreign Currency in 2022 collected $4,520.82. In conclusion, it is determined that Income Tax and Value Added Tax generate great tax contribution to the canton, because they have a broad tax base, an efficient collection system and the Tax Administration implements effective control measures.